The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9103270
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Quality of Life, Functional Assessment and Associated Psychological Distress in Patients with Hypoallergenic Total Knee Arthroplasty

Abstract: Total knee arthroplasty (TKA) is the final treatment for knee osteoarthritis, and 15–30% of patients show little or no improvement. This high percentage is related to aspects of the surgical technique, the selected implant, and specific patient characteristics. The aim of this study was to analyze whether there are differences in quality of life (QoL) and functional capacity among patients undergoing TKA with conventional implants compared to those treated with hypoallergenic oxinium implants. A pragmatic clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previous studies have focused on the relationship between medical diseases or mental disorders including its treatments and patients sexuality, QoL (general or health related), or selected psychological factors highlighting the relationship between these factors and clinical disorders or its treatments [ 5 , 10 , 11 , 13 , 14 , 15 , 19 , 20 , 23 , 25 , 29 , 34 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. These include, sex and quality of life [ 10 ]; sexual health and dysfunction in patients with rheumatoid arthritis [ 13 ]; sexuality and mental health [ 15 ]; antipsychotic-related sexual dysfunction [ 19 ]; sexual function in chronic illness [ 20 ]; the impact of physical illness on sexual dysfunction [ 23 ]; sexual dysfunction and chronic illness [ 27 ]; sex and chronic physical illness [ 28 ]; comorbidities in male and female sexual dysfunction [ 60 ]; sexual dysfunction and mental health in patients with multiple sclerosis and epilepsy [ 29 ]; psychiatric disorders and sexual dysfunction [ 63 ]; thyroid autoimmune disease impacting on sexual function in young women [ 64 ]; clinical features associated with female genital mutilation/cutting [ 65 ]; QoL after flatfoot surgery [ 33 ]; anxiety and QoL in patients with type 2 diabetes [ 58 ]; QoL and associated psychological distress in patients with knee arthroplasty [ 59 ]; psychological factors as determinants of medical conditions [ 57 ]; sleep disturbance, depression and anxiety in frail patients with atrial fibrillation [ 61 ]; cognitive behavior counseling in preoperative preparation and enhanced recovery after surgery [ …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the relationship between medical diseases or mental disorders including its treatments and patients sexuality, QoL (general or health related), or selected psychological factors highlighting the relationship between these factors and clinical disorders or its treatments [ 5 , 10 , 11 , 13 , 14 , 15 , 19 , 20 , 23 , 25 , 29 , 34 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. These include, sex and quality of life [ 10 ]; sexual health and dysfunction in patients with rheumatoid arthritis [ 13 ]; sexuality and mental health [ 15 ]; antipsychotic-related sexual dysfunction [ 19 ]; sexual function in chronic illness [ 20 ]; the impact of physical illness on sexual dysfunction [ 23 ]; sexual dysfunction and chronic illness [ 27 ]; sex and chronic physical illness [ 28 ]; comorbidities in male and female sexual dysfunction [ 60 ]; sexual dysfunction and mental health in patients with multiple sclerosis and epilepsy [ 29 ]; psychiatric disorders and sexual dysfunction [ 63 ]; thyroid autoimmune disease impacting on sexual function in young women [ 64 ]; clinical features associated with female genital mutilation/cutting [ 65 ]; QoL after flatfoot surgery [ 33 ]; anxiety and QoL in patients with type 2 diabetes [ 58 ]; QoL and associated psychological distress in patients with knee arthroplasty [ 59 ]; psychological factors as determinants of medical conditions [ 57 ]; sleep disturbance, depression and anxiety in frail patients with atrial fibrillation [ 61 ]; cognitive behavior counseling in preoperative preparation and enhanced recovery after surgery [ …”
Section: Discussionmentioning
confidence: 99%
“…As the relationship between MA and PD has been reported in the past, we studied how this psychological disorder affects TKA’s outcomes [ 17 ]. Up to one third of the patients with hypoallergenic TKAs have pre-PD, and their results are clearly inferior to those patients with MA without pre-PD.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that is related to the outcomes in TKA is the psychological status of the patient. Up to one third of the patients that undergo TKA may have psychological distress (PD) [ 16 , 17 ], a term that encompasses a group of psychological symptoms, including anxiety, depression, and somatization, which affect the outcome of the surgery [ 18 , 19 ]. Due to the complex relationship of both MA and PD and according to the worse outcomes of hypoallergenic implants [ 17 ] previously published by our group, we decided to study what grade of PD is present in the patients that undergo TKA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting clinical outcomes after TKAs with hypoallergenic implants for confirmed or suspected metal hypersensitivities have produced conflicting data [ 5 , [12] , [13] , [14] , [17] , [18] , [19] ]. Patients with hypersensitivity confirmed by contact SPT have been shown to have equivalent outcomes to patients with negative SPT receiving the same TKA implants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%